Alternatif Perhitungan RBC (Risk Based Capital) Upaya Menjaga Daya Saing Perusahaan Reasuransi Syariah - Ridarmelli, Ridarmelli; Marsono, A. Dewantoro (Business and Management Review, 2011)
RBC is used to measure the performance of insurance company, (shariah or conventional). RBC is one of the insurance company tools to keep its competitive advantage. Based on 424/ KMK.06/2003 the minimum RBC for insurance and reinsurance company is 120%. This is a descriptive research, the study is conducted to explore a new model to determine the unexpected loss (as mentioned in KMK 424, schedule C) using Loss Distribution Approach (LDA) and Extreme Value Theory (EVT) methods. The result is RBC that calculated using LDA & EVT models shows great performance, above the regulation standard. Back Testing is used to test the validity of the methods, the result:  LDA is a valid model to implement in the insurance or reinsurance company, while EVT is not a valid model. Key words: Unexpected Loss, LDA, EVT, competitive advantage.